The Correlation Study between Students’ Vocabulary Mastery and Descriptive Reading Comprehension - Nur Ekaningsih; Ana Furoida (English Education : English Journal for Teaching and Learning, 2022)
The purpose of this study was to find out if there was a positive correlation between students' vocabulary skills and descriptive reading. These was a correlational research methodology by using test of students’ vocabulary knowledge and assess descriptive reading skills. The study used SPSS to assess the relation between students' vocabulary knowledge and descriptive reading skills. The significant value was 0.000 ≤ 0.005, indicating that there was a relation among vocabulary competency and descriptive reading ability among the students. According to the data, 0.700 is the value of the correlation coefficient. So, based on ranges of correlation from 0.60 up to 0.799, it is clear that there was a strong degree of relevance relationship which means that the correlation was indicating a high level of correlation.